Macroeconomic Aspects of Innovation-Driven Growth of Agribusiness in the Republic of Kazakhstan - MADIYEV, Galizhan; KERIMOVA, Ukilyay; YESPOLOV, Aidos; BEKBOSSYNOVA, Assel; RAKHIMZHANOVA, Gaukhar (Journal of Advanced Research in Law and Economics, 2018)
The goal of the paper is to justify macroeconomic mechanisms and tools for the development of efficient forms of management, including the development of cooperation in agribusiness of the Republic of Kazakhstan, aimed at introducing innovation. The current state of the development of agribusiness in Kazakhstan is evaluated as an object of macroeconomic research, which covers its three main areas: agricultural machine building, agriculture, storage and processing of agricultural products. The specifics of approaches and methods of managing investment and innovation activity and the regulatory function of the state in its economic activities are taken into account in the development of macroeconomic mechanisms. The issues of the private subsidiary farms’ development are considered, measures for increasing the efficiency of their economic and investment-innovation activities are proposed. The prospects for cooperation as a means of strengthening the role of private subsidiary farms are established. Based on generalization of theoretical foundations for the formation of the macroeconomic environment that creates conditions for industrial and innovation-driven growth of agribusiness and following the results of the analysis of its current situation, proposals have been developed to change macroeconomic policies: an increase in aggregate expenditures to a level that ensures full utilization of the resource potential of the sector; activation of investment and innovation activities; revision of all macroeconomic instruments: monetary policy, insurance system, subsidization, regulation of the agricultural market and pricing of agricultural products, which together create the conditions for market players to arrange production on an innovation basis and ensure the sustainability of their functioning.